Les clôtures symboliques des Algériennes: la virginité ou l'honneur social en question - FERHATI, Barkahoum (Clio. Femmes, Genre, Histoire, 2007)
Liée à l'honneur de la famille, la virginité est une question qui a toujours hanté l'esprit des jeunes filles algériennes. Toutes sortes de pratiques sont envisagées par la société pour la préserver. La plus connue est celles du rbat (action de nouer), dit teskar (action de fermer) ou encore tesfah (action de blinder). Au moyen de techniques ritualisées, elle consiste en la « fermeture » symbolique de l'hymen avant la puberté et son « ouverture » symbolique la veille du mariage. La « chemise tachée du sang de la vierge » doit en être la preuve indéniable: elle authentifie que l'honneur de la famille, du groupe, est intact. Lorsque, pour diverses raisons, l'hymen fait défaut, la société déploie toutes sortes de stratégies palliatives. Aujourd'hui, le certificat de virginité et la reconstitution de l'hymen par la chirurgie plastique, l'hyménorrapie ou l'hyménoplastie, viennent renforcer la pratique symbolique du rabt. La question fondamentale que je pose dans cet article est: peut-on envisager de casser la clôture « malléable » de cette « vaste prison » des femmes afin que les Algériennes puissent intégrer la société en tant qu'individus et non en tant qu'emblèmes de l'honneur de la famille?
Keywords: afrique; algérie; anthropologie; approches et analyses; corps; cours; discipline; féminisme islamique; histoire; hymen; patriarcat; premier cycle; rapports sociaux de sexe; ressource en ligne; rituel; régions géographiques; sciences humaines; sex2283; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; virginité

Governing women's morality: a study of Islamic veiling in Canada - Atasoy, Y. (EUROPEAN JOURNAL OF CULTURAL STUDIES, 2006)
The veiling of Muslim women is subject to strongly contested ideas about whether the veil is a symbol of women's subordination to an oppressive tradition or a means of emancipation from that tradition. This article suggests that women's own personal reasons for veiling must be analysed. Data collected from published documents from Muslim organizations allows for demonstration that the veil is configured as central to an Islamic moral code of female modesty. A further analysis of findings from interviews conducted with veiled Muslim women in Winnipeg shows the nuanced ways in which women enact this code.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; anthropologie; approches et analyses; canada; corps; cours; discipline; féminisme islamique; histoire et politique; identité; manitoba; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; sociologie; thématiques; winnipeg

Unveiled Sentiments: Gendered Islamophobia and Experiences of Veiling among Muslim Girls in a Canadian Islamic School - Zine, Jasmin (Equity & Excellence in Education, 2006)
The practice of veiling has made Muslim women subject to dual oppressions–racism and Islamophobia–in society at large and patriarchal oppression and sexism from within their communities. Based on a narrative analysis of the politics of veiling in schools and society, the voices of young Muslim women attending a Canadian Islamic school speak to the contested notion of gender identity in Islam. The narratives situate their various articulations of Islamic womanhood in ways that both affirm and challenge traditional religious notions. At the same time they also are subject to Orientalist representations of veiled and burqa clad women that represent them as oppressed and backward. Focusing on ethnographic accounts of veiling among Muslims girls who attended a gender-segregated Islamic high school in Toronto, this discussion allows a deeper understanding of how gendered religious identities are constructed in the schooling experiences of these Muslim youth. (Contains 11 notes.)
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; corps; cours; discipline; féminisme islamique; intersectionnalité; islamophobie; ontario; patriarcat; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences de l'éducation; sex2283; sexisme; systèmes d'oppressions; thématiques; toronto; voiles islamiques

Veil: veiling, representation, and contemporary art - Tawadros, Gilane; Bailey, David A. (MIT Press ; IVA, 2003)
No single item of clothing has had greater influence on Western images of Middle Eastern and North African women than the veil. The fascination of Western writers, artists, and photographers with the veil reflects the voyeuristic nature of our interest in what is strange and "other." Veil, which accompanies an exhibition organized by the Institute of International Visual Arts in London, explores the representation of the veil in contemporary visual arts. Providing a context for the commissioned essays are a number of classical historical texts crossing religions, cultures, genders, and ages–from Greek myths to articles published in the aftermath of September 11, 2001. Some of the contemporary artists and scholars write autobiographically about the meaning of the veil in their lives. Others take a more political approach, discussing, for example, how the events of September 11 changed the use and reception of veil imagery throughout the world. Still others take a historical approach, examining how nineteenth-century technological developments in travel and photography led to photographic depictions of both the veiled and unveiled body in relation to landscape. A number of essays look at the art historical precedents for the current interest in artwork addressing the veil, while others examine how codes of modesty and gender segregation have affected the making and viewing of films in postrevolutionary Iran. The essays are by Jananne Al-Ani, David A. Bailey, Alison Donnell, Ghazel, Salah Hassan, Reina Lewis, Hamid Naficy, Zineb Sedira, and Gilane Tawadros. The artists represented include Faisal Abdu'Allah, Kourosh Adim, Ghada Amer, Jananne Al-Ani, Farah Bajull, Samta Benyahia, Gaëtan de Clérambault, Marc Garanger, Shadafarin Ghadirian, Group AES, Emily Jacir, Ramesh Kalkur, Shirin Neshat, Harold Offeh, Gillo Pontecorvo, Zineb Sedira, Mitra Tabrizian, and Elin Strand.
Section: 187 p. : illustrations en noir et en coul. ; 22 cm
Keywords: afrique; afrique du nord; approches et analyses; arts; corps; cours; discipline; féminisme islamique; har4610; histoire de l'art; mode; moyen-orient; point de vue situé; premier cycle; régions géographiques; thématiques; vêtements